Relevance of E × B drifts for particle and heat transport in divertors. (1st June 2022) - Tsui, C K; Boedo, J A; Février, O; Reimerdes, H; Colandrea, C; Gorno, S; ,
Abstract: Radial electric fields up to ∼4 kV m −1 are observed in the boundary between the private flux region (PFR) and the scrape-off layer (SOL) driving E × B drifts between the inner and outer targets at speeds up to 2.8 km s −1 in the Tokamak à configuration variable divertor. The resulting E × B fluxes, located in a narrow region ( Δ ρ Ψ < 0.012 in normalized radius or Δ R − R sep <4 mm mapped to the outer midplane) are equivalent to around 20% of the total heat and particle flux to the divertor targets (inner + outer). At the peak E r, the E × B poloidal transport is equivalent to parallel flows with M ∥ ∼ 3. In the snowflake divertor with a second X-point in the outer SOL, the drifts in the PFR-SOL boundary were equivalent to around 30% of the total heat and particle flux to the divertor targets and cover a region ∼50% wider than in the single null ( Δ ρ Ψ ∼ 0.018, Δ R − R sep ∼ 6 mm). The location of the PFR-SOL boundary drift shifts radially in the E ∥ × B direction when reversing the toroidal field direction. Peaks in density and electron pressure have been identified near the primary X-point along with large gradients in density, temperature, and potential, the latter resulting in a local electric field ∼2.7 kV m −1 which drives a drift (1.9 km s −1 ) upwards towards the closed flux surfaces. Floating potential ( V f ) magnitudes up to 75 V (∼2 kTe ) were measured, indicating that V f and parallel currents should not be neglected when estimating plasma potential.